Exploring high temperature responses of photosynthesis and respiration to improve heat tolerance in wheat - Posch, Bradley C (Journal of experimental botany, 2019)
© The Author(s) 2019. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.